2020
DOI: 10.1136/bmjgast-2020-000517
|View full text |Cite
|
Sign up to set email alerts
|

Detection of advanced colorectal neoplasia and relative colonoscopy workloads using quantitative faecal immunochemical tests: an observational study exploring the effects of simultaneous adjustment of both sample number and test positivity threshold

Abstract: ObjectiveWhen screening for colorectal cancer (CRC) using quantitative faecal immunochemical tests (FIT), test parameters requiring consideration are the faecal haemoglobin concentration (f-Hb) positivity cut-off and the number of stools sampled. This observational study explored variation in f-Hb between samples and the relationship between sensitivity for advanced neoplasia (AN, cancer or advanced adenoma) and colonoscopy workload across a range of independently-adjusted parameter combinations.DesignQuantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We have shown that modification of the FIT threshold is one possible approach to mitigate the impact of the disruption given colonoscopy constraints, as it would prioritise individuals at higher CRC risk. 10 , 11 As with any risk-based approach to screening, especially within an established, organised population screening programme, careful consideration of the local context is required. In the Netherlands, the FIT threshold has previously been modified within the national programme 25 and this could thus be considered a relatively easy option to ensure the continuity of CRC screening in the case of colonoscopy constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that modification of the FIT threshold is one possible approach to mitigate the impact of the disruption given colonoscopy constraints, as it would prioritise individuals at higher CRC risk. 10 , 11 As with any risk-based approach to screening, especially within an established, organised population screening programme, careful consideration of the local context is required. In the Netherlands, the FIT threshold has previously been modified within the national programme 25 and this could thus be considered a relatively easy option to ensure the continuity of CRC screening in the case of colonoscopy constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 and Cancer Global Modelling Consortium (CCGMC; www.ccgmc.org ) was established to support decision making in cancer control both during and after the COVID-19 crisis. This study's objective, conducted as part of the CCGMC, focussed on two example approaches to colonoscopy prioritisation: increasing the FIT threshold for referral to diagnostic colonoscopy, so capacity is directed towards those at higher risk, 10 , 11 and extending the recovery period in which missed individuals are caught up, resulting in extension of the screening interval for a larger proportion of the population. A combination of both approaches would also be possible, allowing for a careful trade-off between managing colonoscopy demand and preventing COVID-19-related excess CRC-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the accuracy of FIT and FOBT in stool samples can vary from day to day. This variation can be attributed to several factors, including differences in the intensity of bleeding from the neoplasm daily ( 6 ). We have put forth another possible explanation for the observed fluctuation: Daily stool weight can influence the precision of FIT and FOBT.…”
Section: Hypothesizing Methodsmentioning
confidence: 99%
“…High diagnostic sensitivity may also result in a higher burden of surveillance colonoscopies. 40 See online supplemental material 6.2 for further discussion on the challenges of predicting incidence reduction from precursor detection.…”
Section: Explanatory Text For Each Principlementioning
confidence: 99%